NMR-based metabolomic study of Apulian Coratina extra virgin olive oil extracted with a combined ultrasound and thermal conditioning process in an industrial setting. (30th May 2021) - Del Coco, L.; Girelli, C.R.; Angilè, F.; Mascio, I.; Montemurro, C.; Distaso, E.; Tamburrano, P.; Chiurlia, S.; Clodoveo, M.L.; Corbo, F.; Amirante, R.; Schena, F.P.; et al.
Highlights: NMR-MVA shows the biophenol increase for ultrasound vs traditional extracted EVOO. High concentration of polyphenols was found in ultrasound-extracted Coratina EVOO. Use of new technologies might increase EVOO bioactive composition positively. Abstract: The innovative combination of ultrasound (Us) with a thermal exchanger to produce high quality extra virgin olive oil (EVOO) was studied using Nuclear Magnetic Resonance (NMR) spectroscopy and multivariate analysis (MVA). Major and minor metabolomic components of Apulian Coratina EVOO obtained using the two methods were compared. Early and late olive ripening stages were also considered. An increased amount of polyphenols was found for EVOOs obtained using the Us with respect to the conventional method for both early and late ripening stages (900.8 ± 10.3 and 571.9 ± 9.9 mg/kg versus 645.1 ± 9.3 and 440.8 ± 10.4 mg/kg). NMR spectroscopy showed a significant increase (P < 0.05) in polyunsaturated fatty acids (PUFA) as well as in the tyrosol and hydroxytyrosol derivatives, such as oleocanthal, oleacein, and elenolic acid, for both ripening stages. In conclusion, NMR spectroscopy provides information about the metabolomic components of EVOOs to producers, while the Us process increases the levels of healthy bioactive components.